2016
DOI: 10.21865/ridep42_111
|View full text |Cite
|
Sign up to set email alerts
|

Pérdida y Afrontamiento en Desempleados: Adaptación del Inventario Texas Revisado de Duelo a la Situación de Pérdida de Empleo

Abstract: ResumenEste estudio aplica por primera vez el Inventario Texas Revisado de Duelo (ITRD) en un contexto de pérdida de empleo. Los participantes de este estudio son 217 desempleados de la ciudad de Huelva. Se realiza un análisis de los ítems del instrumento obteniendo una fiabilidad de consistencia interna de .85 y .90 en cada parte del instrumento. El análisis factorial exploratorio extrae dos factores coincidentes con el cuestionario original. Con objeto de obtener evidencias de validez se realiza un análisis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
6
0
2
Order By: Relevance
“…A meta-analysis of longitudinal studies has shown that job loss can cause severe emotional distress (Paul & Moser, 2009). Job loss may yield transient reactions of grief (Brewington, Nassar-mcmillan, Flowers, & Furr, 2004;Climent-Rodríguez, Navarro-Abal, López-López, Gómez-Salgado, & García, 2019;Diaz et al, 2015;cf. Lorenz, Maercker, & Bachem, 2020, who focused on adjustment disorder after involuntary job loss).…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of longitudinal studies has shown that job loss can cause severe emotional distress (Paul & Moser, 2009). Job loss may yield transient reactions of grief (Brewington, Nassar-mcmillan, Flowers, & Furr, 2004;Climent-Rodríguez, Navarro-Abal, López-López, Gómez-Salgado, & García, 2019;Diaz et al, 2015;cf. Lorenz, Maercker, & Bachem, 2020, who focused on adjustment disorder after involuntary job loss).…”
Section: Introductionmentioning
confidence: 99%
“…Un panorama diferente podría hallarse cuando las respuestas del CERQ se focalizan en situaciones problemáticas en particular; por ejemplo, en investigaciones sobre el uso de estrategias cognitivas de regulación emocional en infertilidad (Kraaij et al, 2009) o situaciones de vuelo (Kraaij, Garnefski, & van Gerwen, 2003), los coeficientes presentan magnitudes superiores en comparación a los que resultan cuando se responde el CERQ sin especificar la situación. Por tal motivo, una estrategia para incrementar la confiabilidad de las puntuaciones sería considerar la especificidad situacional de las respuestas, es decir, considerar una evaluación por contexto (p.e., académico) en lugar de algo general, dado que es una tendencia creciente en diversos instrumentos de medición (e.g., Díaz et al, 2016).…”
Section: Discussionunclassified
“…Texas Revised Inventory of Grief adapted to the Job Loss Situation (Díaz et al, 2016): an adaptation of the TRIG, an instrument originally designed to assess the intensity of grief for the loss or death of a loved one, performed in the context of job loss (Faschingbauer et al, 1987). It consists of a total of 21 statements with a five-point Likert-type response format (from completely true to completely false) grouped into two dimensions or scales: Past grief and Current grief.…”
Section: Methodsmentioning
confidence: 99%
“…Díaz et al (2016) carried out a study in which they applied the Texas Revised Inventory of Grief (TRIG) for the first time in a job loss context. The participants in this study, a group of unemployed Spaniards, did not present differences in the intensity of grief due to job loss related to age and sex, but in relation to the length of unemployment and responsibility for family income.…”
Section: Introductionmentioning
confidence: 99%